Implementation of Religious Moderation Attitudes Among Students of the State Hindu College (STAHN) Jawa Dwipa Klaten, Central Java - Pujianto, Eko; Khoiri, Nur; Nurkolis, Nurkolis (Journal of Educational Sciences, 2025)
The issue of religious moderation has become increasingly important in higher education as a foundation for building inclusive and harmonious academic communities. This study aims to describe the implementation of religious moderation attitudes among students at the State Hindu College (STAHN) Jawa Dwipa Klaten, Central Java. This research employed a qualitative descriptive approach, focusing on processes, strategies, and outcomes of religious moderation in academic and non-academic environments. Data were collected through observation, interviews, and documentation, and analyzed using interactive analysis techniques. The findings show that religious moderation is implemented systematically through integrative, participatory, and contextual approaches. The core elements of national commitment, tolerance, anti-violence, and respect for tradition are embedded in the curriculum, student organizations, and community service programs. The institution has successfully built an inclusive academic climate that promotes harmony, mutual respect, and peaceful coexistence. It can be concluded that STAHN Jawa Dwipa Klaten has developed religious moderation as an institutional culture supported by leadership commitment and academic collaboration, thereby serving as a model for Hindu higher education institutions in Indonesia.